Occupational health hazards and use of personal protective equipment among automobile mechanics in Surulere local government area of Lagos State, Nigeria - a descriptive study - Ebenezer Adeiza Ozomata; Emmanuel Friday Osagiede; Thelma Joy Onyebujoh (Occupational Health and Safety Society of Nepal, 2022)
Introduction: The job of an automobile mechanic is associated with hazards, illness, and injuries, which may result in sickness, absenteeism, economic loss, disability, or even death. This study assessed the level of knowledge and workplace safety practice by automobile mechanics. Methods: A descriptive cross-sectional study was carried out among 120 registered automobile mechanics in Surulere Local Government Area of Lagos State, Nigeria. A questionnaire was used to obtain information on socio-demography and occupational health practices. Data entry and analysis were done with Epi-info 3.5.1(2008). Chi-square and Fischer Exact tests were used to test for significance. Results: The respondents were all males with a mean age of 39.9±7.5 years, the majority learned the trade through apprenticeship (95.80%) and on full-time work (98.30%). Most respondents (95.8%) were aware of at least one health problem associated with its hazards. Over 75% of respondents were aware of physical hazards. Over eighty percent (84.17%) of respondents used their own overalls, 40% of them used overalls regularly, and only 26.67% of respondents used overalls appropriately. Conclusion: Many respondents were aware of health problems, occupational hazards, and PPE used in the Automobile workplace but did not translate to good practice of workplace safety as seen in only 1.67%. The respondents did not deem the use of PPE necessary and lack, or inadequate training on the 'how' and 'why' PPE were identified as factors hindering PPE use. Workers' training and adherence monitoring could help improve good workplace safety practices in Lagos, Nigeria.